SPECIFICITY OF PERFORMING KIDNEY TRANSPLANTATION AFTER CHRONIC KIDNEY DISEASE (Innovative Technologica: Methodical Research Journal, 2021)
Kidney transplantation is one of the first disciplines of transplant medicine to be established clinically as the standard of care for patients with end-stage renal disease. The significant advantages of kidney transplantation over hemodialysis in terms of life expectancy and quality, as well as in economic terms, make it the method of choice, especially in relatively young patients. Indications for kidney transplantation are determined jointly by a transplant surgeon and a nephrologist or urologist (or / and a pediatrician). These patients are usually chronic dialysis patients.